PENGARUH PEMBERIAN KOMPOS LIMBAH SAYUR-SAYURAN TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell Arg.) - Kartika, Esra; Nurhidayah, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to study the effect and to obtain the best dose of vegetables waste compost on the growth of the rubber seedlings. The experiment has been conducted at the experimental farm of the Faculty of Agriculture, Riau University Pekanbaru from may to September 2018. The experimental unit was arranged in a Completely Randomized Design (RAL), consisting of 6 treatments: 0, 40, 80, 120,160 and 200 g/seedling and replicated 3 times. Each experimental unit consisted of 3seedlings. Parameters observed were seedling height , increase of stem diameter, number of leaves, length of leaf strands and leaf blade width. Data were analyzed statistically using analysis of variance and the mean of each treatment was compared with Duncan s New Multiple Range Test at level 5 %. The result showed that the dose of vegetables waste compost 200 g/seedling gave a better effect on enhacing the growth of rubber seedling. Keywords :. Hevea brasiliensis Muell Arg., vegetables waste compost.